2022
DOI: 10.1007/s00203-022-02889-8
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion and aggregation properties of Lactobacillaceae strains as protection ways against enteropathogenic bacteria

Abstract: The adhesion and aggregation are characteristic attributes of probiotic strains belonging to Lactobacillaceae genus. Due to these properties the host organisms can avoid colonisation of the intestinal tract by enteropathogenic bacteria. The presented research includes a comparison of the properties of various strains belonging to different Lactobacillaceae species and isolated from different sources The aim of this study was to investigate the ability of Lactocaseibacillus rhamnosus, Lactiplantibacillus planta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 47 publications
3
32
0
Order By: Relevance
“…Characterizing important changes in this family in KPbA mice may ultimately provide promising microbial targets to combat the metabolic disorders caused by malaria. As one of the most common probiotic families (Zawistowska-Rojek et al, 2022), Lactobacillaceae was significantly lower in the WPbA and KPbA groups than in their corresponding control groups, but was less affected by MIF knockout, indicating that it is mainly PbA infection that caused the decrease in Lactobacillaceae.…”
Section: Discussionmentioning
confidence: 89%
“…Characterizing important changes in this family in KPbA mice may ultimately provide promising microbial targets to combat the metabolic disorders caused by malaria. As one of the most common probiotic families (Zawistowska-Rojek et al, 2022), Lactobacillaceae was significantly lower in the WPbA and KPbA groups than in their corresponding control groups, but was less affected by MIF knockout, indicating that it is mainly PbA infection that caused the decrease in Lactobacillaceae.…”
Section: Discussionmentioning
confidence: 89%
“…Of the notable taxa that differed between paired and isolated voles, Anaerostipes and Lactobacillaceae , which had a greater abundance in the fecal communities of paired voles, have previously been associated with putative benefits to host health either through the production of short chain fatty acids (SCFAs) [ 43 , 44 , 45 ] or regulation of pathogen growth and colonization [ 23 , 46 ]. Conversely, several taxa, such as Enterococcus , Metaprevotella , and Staphylococcaceae that had a greater abundance in the fecal communities of isolated voles have previously been associated with disease [ 35 , 42 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to auto-aggregate lactobacilli is an important feature that creates the barrier and hinders patho-genic strains' adhesion (Klopper et al 2018). The value of auto-aggregation depends mainly on the incubation time (Piwat et al 2015;) and on the strain tested (Zawistowska-Rojek et al 2022b). In the current study, the auto-aggregation values ranged from 37% to 89%, depending on the strain used.…”
Section: Lacticaseibacillusmentioning
confidence: 99%
“…In addition, it is suggested that the shape of the bacterial cell is also vital for aggregation; longer cells, due to their larger surface area, are characterised by more significant aggregation. Thanks to this, lactic acid bacterial cells can remain in the host's gastrointestinal tract for a long time (Rajab et al 2020;Zawistowska-Rojek et al 2022b). According to some researchers, bacterial auto-aggregation is correlates with these bacteria's ability to adhere to and colonise the gastrointestinal tract (Hojjati et al 2020).…”
Section: Introductionmentioning
confidence: 99%